'I will not be a 17 year old virgin': female virginity and sexual scripting in graphic narratives for teenagers. Issue 1 (2nd January 2019) - Stamper, Christine N.; Blackburn, Mollie V.
ABSTRACT: This manuscript examines how YA graphic narratives represent sexuality with particular attention to the loss of virginity as experienced by girls and young women. It draws on the notion of sexual scripts, which are the socially learned strategies that signal what makes a situation sexual. Sexual scripts matter because of the expectations that are placed on, especially, teenagers. Through the lens of sexual scripts, we study four graphic narratives that portray young adult women losing their virginity, however they conceptualise that. The focal narratives are Daniel Clowes' Ghost World, Sarah Oleksyk's Ivy, Ariel Schrag's Potential, and Julie Maroh's Blue is the Warmest Color . By looking at the texts through the theory of sexual scripting, these sexual relationships show that these contemporary females are more agentive than those seen in traditional media portrayals. However, they still adhere to many of rules of gendered sexual scripting, such as having men's pleasure foregrounded. Ghost World and Ivy showcase heterosexual encounters in relationships that leave the young women unsatisfied. Potential and Blue is the Warmest Color contrast heterosexual relationships with loving lesbian relationships that provide a stronger emotional connection and greater physical pleasure. Thus, more opportunities for subverting potentially harmful ideologies still exist.